NUMERICAL STUDY OF THE INFLUENCE OF GEOMETRIC PARAMETERS ON THE AVALIABLE POWER IN A SOLAR CHIMNEY - Vieira, R. S.; Garcia, C.; Junior, I. C. A.; Souza, J. A.; Rocha, L. A. O.; Isoldi, L. A.; dos Santos, E. D. (Revista de Engenharia Térmica, 2015)
In the presented work, it is made a numerical study about the main physical principle of a solar chimney (SCPP – Solar Chimney Power Plant) and the influence of some geometric parameters on the available power in the SCPP. The main objectives are to test the applicability of the studied numerical model in future studies of SCPP geometric optimization and to test the action of the collector inlet height (H1) and the chimney outlet diameter (D2) on the available power of the device. For that it is considered an incompressible, turbulent, steady flow with mixed convective heat transfer in a two-dimensional and axisymmetric domain, similar to the one found in a solar chimney. The conservation equations of mass, momentum and energy are numerically solved using the finite volume method, more specifically with the FLUENT software. The classical turbulence modeling (RANS) was used for the turbulence approach with standard model k – ε. The other geometric parameters: collector radius (R) and the inlet and outlet of the turbine section, R1 and R2, are also constant. The verification results indicated a good agreement with those presented in the literature, even using a simplified domain. It was also observed that the H1 parameter is almost insensitive in the solar chimney performance, whereas the D2 variable presented great influence in the available power. The best performance was attained for an intermediate value of D2, D2 = 0.44 m. For this value, the available power was almost 72% and 19% higher from those obtained in the inferior and superior extremes of the studied D2 variable, D2 = 0.22 m and 0.88 m, respectively. It was also observed that there is a very good possibility of optimization of the chimney geometry in future studies.